A Service Quality Analysis in Small Maintenance and Repair Company Using Lean Six Sigma Approach - Kinasih, Restu; Damar, Haunan; Usman, Usman; Zakaria, Fakhmi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study examines service quality in a small maintenance and repair company, using lean six sigma to identify problems and identify errors causing inconsistent service quality. The study used a qualitative approach, incorporating descriptive analytics, to analyze data from observations, customer interviews, and employee interviews in CV. ABC. DMAIC framework is used to find the root cause of the problem, and provides best possible suggestions to improve the quality of the company's services. In this study, it was found that the problem that caused the inconsistent level of service quality was a problem in administrative management there were 3 main errors, there are inaccurate expenses tracking, inaccurate invoices, incomplete job documentation. In improve phase that use FMEA, it was found that the company must further improve job documentation to improve service quality because it has the highest Risk Priority Number.